Milton Santos’ Contribution to the Epistemological Debate in Geography - Oliveira-Neto, Thiago (2018)
This article aims to approach Milton Santos’ contribution for the insertion of theoretical debates within the field of geography, through five books: Por una geografía nueva (The Active Role of Geography: A Manifesto); Espacio dividido (The Shared Space); Espacio, técnica y tiempo (Space, Technical and Time); Naturaleza del espacio (The Nature of Space); Por otra globalización (Toward an Other Globalization: From the Single Thought to Universal Conscience). In this context were highlighted some topics the author worked on: space, territory, and technique, present in the works to a greater or lesser expressiveness.